Opinion: Are Organoids the End of Model Evolution for Studying Host Intestinal Epithelium/Microbe Interactions? - George, Michelle M. (Microorganisms, 2019)
In the pursuit to understand intestinal epithelial cell biology in health and disease, researchers have established various model systems, from whole animals (typically rodents) with experimentally induced disease to transformed human carcinomas. The obvious limitation to the ex vivo or in vitro cell systems was enriching, maintaining, and expanding differentiated intestinal epithelial cell types. The popular concession was human and rodent transformed cells of mainly undifferentiated cells, with a few select lines differentiating along the path to becoming goblet cells. Paneth cells, in particular, remained unculturable. The breakthrough came in the last decade with the report of conditions to grow mouse intestinal organoids. Organoids are 3-dimensional ex vivo “mini-organs” of the organ from which the stem cells were derived. Intestinal organoids contain fully differentiated epithelial cells in the same spatial organization as in the native epithelium. The cells are suitably polarized and produce and secrete mucus onto the apical surface. This review introduces intestinal organoids and provide some thoughts on strengths and weaknesses in the application of organoids to further advance our understanding of the intestinal epithelial–microbe relationship.